Pengaruh Gaya Hidup, Literasi Keuangan, Mental Accounting dan Locus of Control Terhadap Pengelolaan Keuangan Gen-Z - Raisha Adinda Rismarina; Agus Maulana (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
Gen-Z is currently the largest demographic in Indonesia. The financial management of Gen-Z will affect the economic condition of Indonesia. This research uses a quantitative approach, with data processed using the SEM-PLS method. A total of 184 samples were obtained based on purposive sampling method. It was found that lifestyle and financial literacy do not have a significant impact, while mental accounting and locus of control have a significantly positive impact on Gen-Z’s financial management.